(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2010)
Topical gels of Valdecoxib topical gel prepared using different gelling agents (Viz, carbopol, HPMC, sodium alginate, sodium CMC). Formulations were evaluated for pH, rheological behavior, drug content and in vitro drug diffusion. Selected formulations of all the gelling agents appeared to be non-Newtonian and pseudo plastic behavior. Drug content was high (>98 %) in gels. Drug release from the carbopol gels increased with the increase in the concentration of PG up to 10 %. However, drug release decreased as the concentration of the PG increased to 20 %. The drug release increased with the increase in concentration of ethanol. In case of gels containing HPMC, sodium alginate, sodium CMC as gelling agents, addition of PG up to 5 %, increased the release of drug from the gels. However, release decreased with increase in the concentration of PG up to 10 %. In case of HPMC gels, addition of ethanol decreased the release of Valdecoxib from the gels. It is concluded that PG is a good penetration enhancer and carbopol good gelling agent for Valdecoxib gels.